The Implementation of School Based Management in Madrasah Ibtidaiyah - Aceng Jaelani; Moh Masnun (IAIN Syekh Nurjati Cirebon, 2019)
AbstractThis study aims to determine the implementation of School Based Management (SBM) on student learning outcomes at Madrasah Ibtidaiyyah (MI) in Harjamukti District, Cirebon City. The research method adopted in this study was field research. Data collection is done through interviews, observation, and documentation. Data analysis techniques used in this qualitative research was inductive in nature, namely an analysis based on the obtained data. The steps taken were analyzing the data which has been collected; interpreting the data; drawing conclusions through way of thinking based on specific facts, where then directed to general conclusions. The results show that the implementation of SBM at MI in Harjamukti Cirebon District has been running quite effectively and efficiently. This can be seen from the support of all staff, SBM phasing, staff training, budget support and delegation of authority, high academic achievement of students, teachers mastery on materials and appropriate teaching procedures, efficient and effective use of facilities, teacher understanding of the characteristics of groups and individuals, a fun and interactive learning environment and the personality of teachers who can act as role models. Based on various aspects which have been arranged in school-based management, this has implications on improving student learning outcomes at Madrasah Ibtidaiyah in Harjamukti District, Cirebon City. Furthermore, this is evidenced in the school exam results.Keywords: school based management, learning outcomes, madrasah ibtidaiyah AbstrakPenelitian ini bertujuan untuk mengeksplorasi implementasi Manajemen Berbasis Sekolah (MBS) terhadap hasil belajar siswa di Madrasah Ibtidaiyah (MI) Se Kecamatan Harjamukti Kota Cirebon. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian lapangan (field research). Pengumpulan data dilakukan dengan menggunakan wawancara, observasi, dan dokumentasi. Teknik analisis data dalam penelitian ini bersifat induktif, yaitu suatu analisis berdasarkan data yang diperoleh. Langkah yang dilakukan adalah Menelaah data yang berhasil dikumpulkan, menafsirkan data, kemudian mengambil kesimpulan secara induktif, yaitu penarikan kesimpulan dengan cara berfikir berdasarkan fakta- fakta khusus, kemudian diarahkan kepada penarikan kesimpulan umum. Hasil penelitian menunjukkan bahwa penerapan MBS di MI se Kecamatan Harjamukti Cirebon sudah berjalan cukup efektif dan efesien, hal ini tercermin dari dukungan seluruh staf & pelatihan staf, pentahapan MBS, dukungan anggaran dan pendelegasian wewenang, prestasi akademik siswa yang tinggi, penguasaan guru terhadap bahan dan prosedur mengajar yang tepat, pemanfaatan fasilitas secara efisien dan efektif, pemahaman guru tentang karakteristik kelompok dan perorangan, lingkungan belajar yang menyenangkan dan interaktif serta kepribadian guru yang bisa menjadi teladan. Berdasarkan berbagai aspek yang telah tersusun dalam manajemen berbasis sekolah, hal tersebut berimplikasi terhadap peningkatan hasil belajar siswa di Madrasah Ibtidaiyah se Kecamatan Harjamukti Kota Cirebon. Hal ini dibuktikan dalam hasil ujian sekolah.Kata kunci: manajemen berbasis sekolah, hasil belajar, madrasah ibtidaiyah.